The impact of board gender composition on dividend payouts - Chen, Jie; Leung, Woon Sau; Goergen, Marc (Journal of Corporate Finance, 2017)
This paper investigates whether female independent directors are more likely to impose high dividend payouts. We find evidence that firms with a larger fraction of female directors on their board have greater dividend payouts. This finding is robust to alternative econometric specifications, and alternative measures of dividend payouts and female board representation. The positive effect of board gender composition on dividends remains when we employ propensity score matching, the instrumental variable approach, and difference-in-differences approach to address potential endogeneity concerns. Furthermore, we find that board gender composition significantly increases the dividend payout only for firms with weak governance, suggesting that female directors use dividend payouts as a governance device.